Gold Mining Conflict Between the Community and the Government in Nagari Simpang Tonang, Dua Koto District, Pasaman Regency. - Ifti Syariah; Endrizal; Yetty Oktayanti (Kirana Publisher (KNPub), 2024)
This paper is entitled